A relação cidade-campo em Campina Grande a partir da produção do algodão colorido - Silva, Rafaela Fernandes e (2011)
The ancient city-country dichotomy has been diluted with the news changes, making a dialectical unity between these two spatiality. The news relationships city-country is based in exchange of information and technology by the city. It s creates a new agricultural activitie s arrangement. With this changes arises the scientific agriculture, guide to market economy according urban and industrial demands. The economic dynamics of the Campina Grande city is based in the agricultural production since its foundation. However, in the last years, from the work of Embrapa Cotton has been begun changes in agricultural production process, especially in cotton cultivation, stimulated by researches and experiments developed based on technology and information. Campina Grande had a strong participation of the cotton industry during its process of expansion and socioeconomic formation. This city developed based in capital accumulation generated by cotton businesses. Nowadays, Campina Grande has a new cotton history: the creation of color cotton and the production of its derivatives. By the way, the city has many cooperatives responsible for export and for manufacturing of finals products, such as clothes, accessories and decoration items. Among the cooperatives that operate in the cotton sector, stands out Coopnatural, which works with organic colored cotton. In this context, the present research has aimed analyze the relationship between city and country in the Campina Grande city, from cotton color. The color cotton culture wasn t so influent in the city as the color culture developed in the end century 19 and begin 20, but has influenced on the textile industry. This analysis was realized whit literature about themes relevant to the research, as well empirical researchers in the production s fields and in the establishments responsible for production of cotton color s derivatives.